2021
DOI: 10.1302/2058-5241.6.200080
|View full text |Cite
|
Sign up to set email alerts
|

Full endoscopic surgery for thoracic pathology: an assessment of supportive evidence

Abstract: In the last five years, surgeons have applied endoscopic transforaminal surgical techniques mastered in the lumbar spine to the treatment of thoracic pathology. The aim of this systematic review was to collate the available literature to determine the place and efficacy of full endoscopic approaches used in the treatment of thoracic disc prolapse and stenosis. An electronic literature search of PubMed, Embase, the Cochrane database and Google Scholar was performed as suggested by the Preferred Reporting Items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
(18 reference statements)
2
14
0
Order By: Relevance
“…The review included papers from 2006 to 2020 comprising 17 patient series, 1 cohort study, and 13 case reports with 1 to 3 patients. 8 In 460 patients, complications reported were dural tears (2%), transient paresthesia (2%), revision surgery (1.5%), neurologic injury (0.6%), and epidural hematoma (0.6%). [19][20][21][22][23][24][25][26][27][28][29][30][31][32] The review concluded that there was clear evidence for a lower complication rate and shorter hospital stay with endoscopic thoracic spine surgery approaches versus open approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The review included papers from 2006 to 2020 comprising 17 patient series, 1 cohort study, and 13 case reports with 1 to 3 patients. 8 In 460 patients, complications reported were dural tears (2%), transient paresthesia (2%), revision surgery (1.5%), neurologic injury (0.6%), and epidural hematoma (0.6%). [19][20][21][22][23][24][25][26][27][28][29][30][31][32] The review concluded that there was clear evidence for a lower complication rate and shorter hospital stay with endoscopic thoracic spine surgery approaches versus open approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there were no reported cases in the endoscopic experience of wrong-level surgery, vertebral column instability, cerebrospinal fluid leaks/pleural fistulas, thoracic viscera injury, or intercostal neuralgia. 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Thoracic endoscopes differ from other spinal endoscopes in the following ways ( Figure 1 ): They are angled at 45°. This allows to work with a steeper access route and much shorter in length as the thoracic spine does not have much soft tissue cover dorsally [ 2 , 3 , 12 ] They are smaller in diameter to accommodate space restriction in the thoracic spine Endoreamers/endodrills are available in various sizes and angles. They are used for undercutting the superior facet or removal of a part of the vertebral body.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, it is very important to identify the entry level of the magna radicular artery and avoid ligating it to prevent paraplegia caused by spinal cord infarction [ 7 ]. Overall, complications from open surgery are reported to occur in over 25% of patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%